VD_FINDINFO Jug / 2025 / 292 vom 22. Januar 2025 - VD Tribunal cantonal (2025)
VOIES DE FAIT, INJURE, MENACEDROIT PÉNAL, SURSIS À L'EXÉCUTION DE LA PEINE | 126 al. 1 CP, 177 al. 1 CP, 180 al. 1 CP, 34 CP, 46 al. 2 CP